2006
DOI: 10.1123/jtpe.25.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Student Teachers’ Implementation of a Curricular Innovation

Abstract: This study examined 49 student teachers’ actions and perspectives when implementing a curricular innovation (the tactical games approach). Data were collected via videotaped lessons, interviews, and follow-up questionnaires. Questions for interviews and questionnaires were pilot tested and data were analyzed using the constant comparison method. Videotape analysis was facilitated by Noldus’s Observer (4.0) software and was tested for interobserver reliability. Results revealed that pupils were actively engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
2
24
0
2
Order By: Relevance
“…Brooker et al (2000) posited that support from research colleagues through university collaboration was important as it provided teachers with research knowledge that allowed them to overcome the initial de-skilling that was occurring when using Games Sense for the first time. In the same way O'Donovan et al (2010) (Stran and Curtner-Smith 2009), to provide opportunities for teachers to practice (Wright et al 2006) and support them in transferring theory to the classroom (McMahon and MacPhail 2007). In his role as a teacher-as-researcher Casey (see showed how theory and practice could be melded together to support and enhance his sustained use of MBP.…”
Section: University/teacher Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brooker et al (2000) posited that support from research colleagues through university collaboration was important as it provided teachers with research knowledge that allowed them to overcome the initial de-skilling that was occurring when using Games Sense for the first time. In the same way O'Donovan et al (2010) (Stran and Curtner-Smith 2009), to provide opportunities for teachers to practice (Wright et al 2006) and support them in transferring theory to the classroom (McMahon and MacPhail 2007). In his role as a teacher-as-researcher Casey (see showed how theory and practice could be melded together to support and enhance his sustained use of MBP.…”
Section: University/teacher Collaborationmentioning
confidence: 99%
“…However, many other authors have gone further and suggested that the links and support mechanisms created between universities and schools, and researchers and teachers, were important in the successful adoption of MBP. Barrett and Turner (2000), Brooker et al (2000), McCaughtry et al (2004), McNeill et al (2004), MacPhail, Gorely et al (2008, O'Donovan et al (2010), and Wright, McNeill, Fry, Tan and Tan (2006) all endorsed the importance of school/university collaborations in supporting the teachers' ability to move the theory of the model into their classroom and subsequently engage in research-informed teaching. Brooker et al (2000) posited that support from research colleagues through university collaboration was important as it provided teachers with research knowledge that allowed them to overcome the initial de-skilling that was occurring when using Games Sense for the first time.…”
Section: University/teacher Collaborationmentioning
confidence: 99%
“…PSTs did, however, find opportunities to incorporate aspects of SE approach into their teaching. Wright et al (2006), who found that the PETE course could be an influential factor in inspiring PSTs to implement an innovative teaching approach to games teaching during their school placements. As part of drawing from the formal learning of the course, the PGCE cohort itself provided significant learning support via a variety of mechanisms.…”
Section: Some Of Them Are Willing To Take Great Risks Thomas With Thmentioning
confidence: 99%
“…A questão é como podemos nós, como educadores de professores de educação física, estruturar nossos programas para facilitar nossos alunos dentro e através do processo de mudança, para que possamos produzir graduados que estejam dispostos a aceitar a mudança como parte de seu ensino e desenvolvimento profissional (Wright et al, 2006). …”
Section: Caminhos Possíveisunclassified